2010
DOI: 10.3382/ps.2009-00608
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydrated sodium calcium aluminosilicate and yeast cell wall on counteracting aflatoxicosis in broiler chicks

Abstract: The objective of this research was to determine the efficacy of 2 types of adsorbents [hydrated sodium calcium aluminosilicates (HSCAS) vs. a combination of clay and yeast cell wall] in preventing aflatoxicosis in broilers. A total of 275 one-day-old birds were randomly divided into 11 treatments, with 5 replicate pens per treatment and 5 chicks per pen. The 11 treatments included 3 diets without any adsorbent containing either 0, 1, or 2 mg/kg of aflatoxin B1 (AFB1) plus 8 additional treatments employing 2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
49
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 19 publications
13
49
0
3
Order By: Relevance
“…These effects of Humate might be attributed to mycotoxin adsorption, ability to block colonization of pathogens in the gastrointestinal tract, inhibitory effect on liver antioxidant depletion and growth promoter (Jansen van Rensburg,et al, 2006). Similar results were obtained by Sehu et al (2007) and Zhao et al (2010) who concluded that HSCAS at 5% concentration could significantly and completely ameliorate the growth-depressing effect of aflatoxin B1 as silica binders have been shown to bind the toxins in the digestive tract, making them unavailable for gut absorption and allowing the mycotoxin to pass harmlessly through the animal. The β-carbonyl portion of the aflatoxin molecule binds to the uncoordinated edge site of aluminum ions of the HSCAS, making the aflatoxin molecule unavailable for adsorption (Sarr et al, 1990).…”
Section: Growth Performance Parameterssupporting
confidence: 79%
“…These effects of Humate might be attributed to mycotoxin adsorption, ability to block colonization of pathogens in the gastrointestinal tract, inhibitory effect on liver antioxidant depletion and growth promoter (Jansen van Rensburg,et al, 2006). Similar results were obtained by Sehu et al (2007) and Zhao et al (2010) who concluded that HSCAS at 5% concentration could significantly and completely ameliorate the growth-depressing effect of aflatoxin B1 as silica binders have been shown to bind the toxins in the digestive tract, making them unavailable for gut absorption and allowing the mycotoxin to pass harmlessly through the animal. The β-carbonyl portion of the aflatoxin molecule binds to the uncoordinated edge site of aluminum ions of the HSCAS, making the aflatoxin molecule unavailable for adsorption (Sarr et al, 1990).…”
Section: Growth Performance Parameterssupporting
confidence: 79%
“…Aluminosilicates efficiently absorb aflatoxin, but have not been able to effectively absorb trichotecenes (Phillips 1999). The effect of E-GM to improve the adverse consequences of mycotoxins on chickens performance, immunity, blood haematological and biochemical indices has been previously studied (Raju & Devegowda 2002;Aravind et al 2003;Girish & Devegowda 2006;Zhao et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the mentioned experiments, crystalized toxin have been used to apply contamination in diets (Girish & Devegowda 2006;Zhao et al 2010), but naturally mould-contaminated diet supplied in this experiment. Additionally, research on the use of high-performance liquid chromatography (HPLC) to detect mycotoxins at the levels of this trial is less investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that AFB 1 has a range of negative effects on poultry health, including poor performance (Oguz and Kurtoglu, 2000;Magnoli et al, 2011), liver and kidney lesions (Ortatatli et al, 2005), immunity damage (Marin et al, 2002), and hematology problems (Zhao et al, 2010). Moreover, the tissue deposition and residue of AFB 1 in poultry has also been determined (Oliveira et al, 2000(Oliveira et al, , 2003.…”
mentioning
confidence: 99%